Longitudinal Analysis of Marathon Runners’ Psychological State and Its Relationship With Running Speed at Ventilatory Thresholds - Larumbe-Zabala, Eneko; Esteve-Lanao, Jonathan; Cardona, Claudia A.; Alcocer, Alberto; Quartiroli, Alessandro (Frontiers in Psychology, 2020)
Psychological variables such as motivation, self-efficacy, and anxiety have been widely studied in marathon runners, usually within the framework of Bandura’s theory of self-efficacy. It is also assumed a link between self-perceived fitness and physiological performance parameters such as speed at ventilatory thresholds and running economy. The purpose of this paper is to describe longitudinal trends of self-perceptions and examine their link to physiological performance parameters over time. Sixteen healthy recreational marathoners (8 males and 8 females), aged M = 37.6 (SD = 3.9) who were about to participate in a major marathon agreed to participate. After 3 months of regular training and competition in shorter distances, all participants trained during a 16-week macrocycle under the supervision of the same coaching staff. At 4-week intervals, the participants responded five times the Podium questionnaire, measuring self-perceived psychological state relative to the upcoming race, and performed five exercise performance parameters tests. Linear mixed-effects models were used to analyze the trends and associations. In general, Podium questionnaire scores were within the standard range, with the lowest values at the beginning and the highest values closer to race day. Although only perceived fitness (p < 0.001, Cohen’s f2 = 1.19) and somatic anxiety (p < 0.001, f2 = 0.32) showed large effect sizes for the whole longitudinal period, other partial increases were found between time points. All physiological performance parameters presented significant improvements over time (Aerobic Threshold speed, p < 0.001, f2 = 1.04; Anaerobic Threshold speed, p < 0.001, f2 = 0.498; Running Economy in VO2, p < 0.001, f2 = 0.349; Running Economy in energy, p = 0.024, f2 = 0.197). The analysis of changes between consecutive time points revealed that improving perceived physical condition predicted improving self-efficacy (p < 0.001, f2 = 1.33), and improvements in motivation were predicted by improvements in either self-efficacy (p < 0.001, f2 = 0.36) or perceived physical condition (p = 0.003, f2 = 0.17). Improvements in perceived fitness, self-efficacy and motivation were associated with small effect-size improvements (decreases) in anxiety. None of the physiological performance parameters was shown to predict changes in psychological variables, although their general trends over time correlated. The results have practical implications for sport psychologists and running coaches, supporting the need for integrated working.